Alzheimer's Disease: Targeted Magnetic Nanoparticles for Remote Magnetothermal Disruption of Amyloid‐β Aggregates (Adv. Healthcare Mater. 14/2015). Issue 14 (7th October 2015) - Loynachan, Colleen N.; Romero, Gabriela; Christiansen, Michael G.; Chen, Ritchie; Ellison, Rachel; O'Malley, Tiernan T.; Froriep, Ulrich P.; Walsh, Dominic M.; Anikeeva, Polina
Abstract : On p. 2100, P. Anikeeva and co‐workers demonstrate a technique using remotely triggered local heating to disaggregate deposits of the protein Aβ(1–42), which plays an important role in Alzheimer's Disease pathogenesis. The cover image shows neural network (green) overlayed with amyloid beta plaques (red) that are decorated with magnetic nanoparticles (blue). The glow around the blue spheres represents heat dissipation by nanoparticles, which induces disaggregation of the plaques.